2010
DOI: 10.1111/j.1755-3768.2009.01583.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative DNA damage in patients with cataract

Abstract: ABSTRACT.Purpose: This study examines the levels of oxidative damage in patients with cataract. Methods: Blood samples were collected from 60 patients with cataract and 60 age-and gender-matched healthy individuals to measure 8-hydroxy 2-deoxyguanosine (8-OHdG) and malondialdehyde (MDA) levels. Results: A significant difference was observed in leukocyte 8-OHdG levels in patients with cataract in comparison with healthy persons (p < 0.001). Similarly, a significant difference was observed in plasma MDA levels i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 38 publications
4
34
0
Order By: Relevance
“…14,18 Oxidative stress is proved to cause DNA damage and subsequent cataract formation. 19,20 Blue Mountain Eye Study proved antioxidants intake, including beta-carotene, zinc, and vitamins A, C, and E, reduced nuclear sclerosis cataract formation. 21 Sorte et al 20 examined DNA damage amounts in lens epithelial cells right after cataract surgery and found that DNA damage products were noted maximally in C cataract subject samples.…”
Section: Eyementioning
confidence: 99%
“…14,18 Oxidative stress is proved to cause DNA damage and subsequent cataract formation. 19,20 Blue Mountain Eye Study proved antioxidants intake, including beta-carotene, zinc, and vitamins A, C, and E, reduced nuclear sclerosis cataract formation. 21 Sorte et al 20 examined DNA damage amounts in lens epithelial cells right after cataract surgery and found that DNA damage products were noted maximally in C cataract subject samples.…”
Section: Eyementioning
confidence: 99%
“…Previous studies have shown a decrease in the systemic level of antioxidant enzymes such as superoxide dismutase and catalase and an increase in oxidative degradation products in cataract patients [4,5,6]. The biomarker of oxidative DNA damage, 8-hydroxydeoxyguanosine (8-OHdG), significantly increased in leukocytes and serum of cataract patients [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The biomarker of oxidative DNA damage, 8-hydroxydeoxyguanosine (8-OHdG), significantly increased in leukocytes and serum of cataract patients [4,5]. Recently, several studies reported the association between genetic polymorphisms of antioxidant enzymes/DNA repair enzymes [7,8,9,10,11] and ARC.…”
Section: Introductionmentioning
confidence: 99%
“…This result was in line with a study that found elevated levels of 8-OH-Gua, a marker of oxidative DNA damage, in the leukocytes of patients with cataract. 40 However, we did not find the correction of the DNA damage with the genotypes. This may be due to the nature of the local lesion (lens) in ARC.…”
Section: Discussionmentioning
confidence: 53%